John Paul II: His Life His Pontificate - Vatican Television Center (Italy HDH Coomunications SRL, 2002)
Documentary biography of Pope John Paul II.
Documentary biography of Pope John Paul II.
A documentary presentation of the life and pontificate of Pope John Paul II, produced by the Vatican Television Center.
Keywords: General audience; Papacy